Madinan “Amal” And Living Sunna: A Conceptual Comparison; Islamic Jurisprudence - Daud Salman (Jurnal Studi Islam Indonesia (JSII), 2024)
The origin of Islamic law is explicitly stated in many orthodox resources of the principles of jurisprudence (Usul-fiqh). At the dawn of the twentieth century, Western scholars, notably Joseph Schacht, engaged fervently in studying the origins and evolution of Islamic jurisprudence, advancing numerous theories in the process. From the historical studies of the sources of the early fiqh Mezhab such as Muwatta, the term Living Tradition or Living Sunna emerged into the continuum of Islamic law. This work draws on source material from different Islamic resources to run a conceptual comparison between “Madinan amal” and “Living Sunna”. Living Sunna implies “amal’ in a wider scope. Living sunna is purposefully derived from the understanding of “amal” to give legal authority to any established practice, custom, or culture of a people, even if it is against the text, as long as it passes the repugnancy and public policy tests. Although the concepts are not absolutely accepted as sources of Islamic law, they give a strong indication of the inevitability of localization of ijtihad and fatwa..